A Mild Phenotype of Severe β+ Thalassemia in a 16-Month-Old Boy. Issue 3 (April 2018) - Akinbami, Anthony O.; Sobota, Amy E.; Luo, Hong-Yuan; Chui, David H.K.; Steinberg, Martin H.
Abstract : β thalassemia is characterized by a deficient production of functional β-globin chains and a relative excess of α-globin chains. An extremely diverse clinical spectrum—asymptomatic to transfusion-dependent—is primarily due to homozygosity or compound heterozygosity for the very large number of β-thalassemia-causing mutations, along with interacting mutations that affect the α-globin and γ-globin genes and their expression. We report a case of a 16-month-old boy who was initially diagnosed with iron deficiency anemia until he was later found to be homozygous for a severe β-thalassemia genotype with a mild hematologic phenotype. This was likely as a result of his ability to produce high levels of fetal hemoglobin.